Divergent Palladium‐Catalyzed Tandem Reaction of Cyanomethyl Benzoates with Arylboronic Acids: Synthesis of Oxazoles and Isocoumarins. Issue 9 (3rd April 2020) - Dai, Ling; Yu, Shuling; Xiong, Wenzhang; Chen, Zhongyan; Xu, Tong; Shao, Yinlin; Chen, Jiuxi
Abstract: A palladium‐catalyzed tandem reaction of cyanomethyl benzoates with arylboronic acids has been achieved. Substitution at the 2‐position of cyanomethyl benzoates was found to be crucial for the selective synthesis of oxazoles and isocoumarins. Cyanomethyl benzoates afforded 2, 4‐diaryloxazoles as products, while 2‐benzoyl‐substituted cyanomethyl benzoates delivered 3‐benzoyl‐4‐aryl‐isocoumarins selectively. Furthermore, a possible mechanism for the selective reaction of cyanomethyl benzoates with arylboronic acids was discussed. Abstract :